2020
DOI: 10.1007/s00380-020-01684-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drug-eluting stents vs. drug-coated balloon after rotational atherectomy for severely calcified lesions of nonsmall vessels

Abstract: Calcified lesion is a risk factor for adverse events, even in the drug-eluting stent (DES) era. Recently, drug-coated balloon (DCB) has been shown to have favourable results for in-stent restenosis and small vessels, but its results for calcified lesions are unknown. This study aimed to clarify the rotational atherectomy (RA) and DCB results for calcified lesions of nonsmall vessels. A total of 194 consecutive de novo lesions from 165 cases underwent RA for calcified lesions of nonsmall vessels between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Data on the treatment of calcified lesions were lacking in the studies included in this meta-analysis. Devices such as cutting and scoring balloons, rotational atherectomy, laser coronary atherectomy are used for the treatment of severe calcified lesions, and study also showed that there was no significant difference in 1-year MACEs between DCB and DES after rotational atherectomy 29 . However, rotational atherectomy and laser coronary atherectomy may lead to increased operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the treatment of calcified lesions were lacking in the studies included in this meta-analysis. Devices such as cutting and scoring balloons, rotational atherectomy, laser coronary atherectomy are used for the treatment of severe calcified lesions, and study also showed that there was no significant difference in 1-year MACEs between DCB and DES after rotational atherectomy 29 . However, rotational atherectomy and laser coronary atherectomy may lead to increased operative time.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains potential complications including suboptimal dilatation, dissections, plaque shift, elastic recoil, and vessel perforation with high-pressure balloon inflation (24). Iwasaki et al (21) chose rotational atherectomy which has been demonstrated a preferred choice in calcified lesions in both DCB and stent group for balloon or stent delivery and expansion, as it could reduce calcified plaque. For DCB, lesion preparation might be more important without stent implantations due to elastic recoil and dissections.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, those results included BMS as a control, which has been rarely applied and not recommended for PCI by the recent guidelines. With the development and advance of DCB, there were several studies that used DCB for treating with de novo non-small vessels (17)(18)(19)(20)(21). Lin et al (22) did a meta-analysis in de novo large vessels, though remained some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RA might prevent the polymer damage, when DES was delivered to the calcified lesions [30]. Although the initial results of debulking using RA was not satisfactory, the debulking might have developed with the aid of imaging devices and drug-coated balloon in Japan [31][32][33][34][35]. Furthermore, the long-term outcomes following RA with plain old balloon angiography was acceptable when the target lesions were limited to large coronary arteries (diameter ≥ 3 mm) [36].…”
Section: Aim Of Ramentioning
confidence: 99%